Sains, Teknologi, Dan Nilai-Nilai Moral - Muhammad AR (Elkawnie: Journal of Islamic Science and Technology, 2016)
This article explains about sciences, technology its relation to moral values. The existence of sciences and technology seems to be more beneficial for human beings in implementing their activities in their daily life. It is suffice to say that sciences and technology can reduce human involvement in doing something. It can help mankind from working hard. On the one other hand, some people say that sciences and technology will be dangerous for human beings, for examples, nuclear weapons, chemical weapons, tanks, scud, and other sophisticated guns or weapons which are produced by mankind exclusively for massacring and killing enemies----human beings. Therefore, sciences and technology must be controlled by those who have moral values and religious teachings. Those who are behind the sophisticated technology should be inculcated moral values into their heart and mind. Actually, Islam is not against development and modern technology but it supports and facilitates them as long as it is beneficial for human beings. We do not have to put a blame on sciences and technology for the Muslims scholars and Muslims scientists themselves had given sAl-Ghazali, Ibnu Sina, Ibnu Rusyd, Ibnu Khaldun, Al-Tabari, Al-Kindi, Al-Jabeer, Al-Khawarizmi, Ibnu Badjah, Baiquni, Al-Farabi, Al-Razi, Omar Khayam, dan Al-Mas’udi toward modern sciences and particularly to the West (Andalusia). They had been contributing sciences and knowledge to the people both in the East and in the West which were introduced by the kingdom of Bani Abbasiyah and Bani Umayyah. Historically, Islam had been contributing sciences and technology to the Europe for more than five centuries. Unfortunately, when non-Muslims conquered Muslims countries they gave two choices for Muslims---becoming Christians or killed! Most of them were killed and some of them escaped to North Africa and Middle East. All muslims schools and libraries were burned by the conquerors. This was the worst circumstances faced by Muslims in Andalus (Spain), Bosnia Herzegovina, Kossovo, Myanmar and Iraq.